Isolation and characterization of polyhydroxyalkanoate (PHA)-producing, cellulolytic bacteria from municipal wastewater - Ernie Eileen Rizlan Ross,; Ishak Zubir,; Wan Razarinah Wan Abdul Razak,; Farida Zuraina Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Polyhydroxyalkanoates (PHA) are linear bio-esters produce in nature by certain microorganisms particularly when subjected to limited nutrients sources such as nitrogen while carbon sources are at abundance. PHA has attracted tremendous amount of attention from scientists globally due to their biodegradable property as environment-friendly alternative to petrochemical based plastics. However, the biggest drawback in using PHA is their high production cost. The aims of this study are to assess and characterise PHA-producing bacteria from municipal wastewater and compare their efficiencies in PHA production. A total of 34 out of 282 bacterial isolates from wastewater showed the ability to produce PHA using Sudan Black B staining. These isolates were then subjected to cellulase activity screen using carboxymethyl cellulose (CMC) agar. Two out of the 34 isolates were showed promising cellulose degrading capability and the cellulolytic activities were studied at 24, 48 and 72 hours of incubation respectively. The PHA production efficiencies of both isolates UiTM-E1 and UiTM-E2 were then compared using mineral salt media (MSM) supplemented with 1% and 2% glucose at 24, 48 and 72 hours of incubations respectively. Isolate UiTM-E2 showed the highest PHA production at 36.93% of its cell-dry weight (CDW) at 48 hours incubation.